Role of biobanking in the development of personalized medicine in Russia and the world - M. S. Pokrovskaya; A. L. Borisova; A. V. Kiseleva; A. I. Ershova; A. N. Meshkov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
To implement a modern personalized approach in practical healthcare, the latest biomedical technologies should be developed and genetic research should be performed. The analysis of a substantial quantity of data is essential for the investigation of the prevalence of genetic risk factors for various diseases, drug resistance genes, the development of genetic panels to determine the individual risk of pathologies, as well as the creation of genetic risk scores. The review demonstrates through the use of illustrative examples that contemporary biobanks have become a vital component in the field of genetics research, both in Russia and globally. These specialized institutions are capable of accumulating, storing, and utilizing a substantial quantity of biological samples and related data, which is essential for advancing genetic research. The data collected in biobanks and associated clinical information form the basis for large-scale genetic studies conducted in different countries. The efficacy of genetic advancements, such as the early diagnosis of diseases, is contingent upon the number of biobanks, the establishment of collaborative networks among them, and the capacity to leverage digital platforms uniting diverse databases. Biobanks and biobanking have emerged as the foundation for the advancement of personalized medicine.